Peran Ibu dalam Pendidikan Karakter Anak Usia Dini Menurut Pandangan Islam - Rianawati Rianawati (PSGA LP2M IAIN Pontianak, 2014)
The article elaborates the important roles of mothers in child’s education. Nowadays, educational issues still becomes a trending topic and are often talked from many point of views, however, the most talked topic is about child’s character building. Character psychologically guides a child to adapt to various environments. Besides, character becomes”a guide” to perform good or bad action. The character is also a factor whether the child be able to adapt to heterogeneous condition. Furthermore, mothers is truly a main educator to create a strong character in a child. Nevertheless, in a real life, there are still mothers who have not properly their job in educational issue. In order to grow the good character in a child, a mother should have a responsibility and proper knowledge. On the other hand, a mother should implement an educational method based on children’s age. Moreover, an upbringing style in a family determines the success of the child’s education.